91.3k views
3 votes
Given: T is the midpoint of JK¯¯¯¯¯JK¯, JK = 5x – 3, and JT = 2x + 1. Determine the length of JK¯¯¯¯¯JK¯

User DanY
by
5.9k points

2 Answers

2 votes

K where T is the midpoint. J >>>>> T >>>>> K.

JK = 5x - 3

JT = 2x + 1

Because T is the midpoint, it means that JT = TK

So, JT + TK = JK

(2x + 1) + (2x + 1) = 5x - 3

4x + 2 = 5x - 3

4x - 5x = -3 - 2

-x = -5

x = 5

JK = 5x - 3

JK = 5(5) - 3

JK = 25 -3

JK = 22

The length of JK is 22.

User Miroslav Holec
by
6.2k points
3 votes
JK where T is the midpoint. J >>>>> T >>>>> K.

JK = 5x - 3
JT = 2x + 1

Because T is the midpoint, it means that JT = TK
So, JT + TK = JK

(2x + 1) + (2x + 1) = 5x - 3
4x + 2 = 5x - 3
4x - 5x = -3 - 2
-x = -5
x = 5

JK = 5x - 3
JK = 5(5) - 3
JK = 25 -3
JK = 22

The length of JK is 22.
User Yutaka
by
5.8k points